SISTEM INFORMASI MONITORING AKTIVASI METERAN PRABAYAR BERBASIS WEB PADA PT. PLN (PERSERO) ULP KRUENG GEUKUEH - Rizky Putra Fhonna; Rafika (Jurnal Sains dan Teknologi, 2021)
Processing data and information quickly and accurately is needed. To get it, it must be supported by a technology that is appropriate and useful and relevant for its application. Especially for PT. PLN (Persero) ULP Krueng Geukueh which is a company that manages all aspects of electricity to the aspect of meter activation, both prepaid and postpaid. Where when the staff activates the meter, they still carry out the data collection system and record data and information using the manual method, namely using Microsoft Excel and an agenda book. From these problems raised the idea to create a web-based information system, which can perform meter activation data processing. This web-based information system design uses PHP and MySQL. With the prepaid meter activation data collection system at PT. PLN (Persero) ULP Krueng Geukueh, staff or employees in the energy transaction division can input meter activation data, delete data, add data, view meter activation data and print prepaid meter activation data reports quickly and efficiently